A real-world pharmacovigilance study of FDA adverse event reporting system events for diazepam - He, Weizhen; Wang, Yang; Chen, Kaiqin (Frontiers in Pharmacology, 2024)
BACKGROUND: Diazepam, one of the benzodiazepines, is widely used clinically to treat anxiety, termination of epilepsy, and sedation. However, the reports of its adverse events (AEs) have been numerous, and even fatal complications have been reported. In this study, we investigated the AEs of diazepam based on real data from the U.S. Food and Drug Administration Adverse Event Reporting System (FDA). METHODS: Disproportionality in diazepam-associated AEs was assessed through the calculation of reporting odds ratios (RORs), proportional reporting ratios (PRRs), Bayesian confidence-propagation neural networks (BCPNNs), and Gamma-Poisson contractors (GPSs). RESULTS: Among the 19514140 case reports in the FAERS database, 15546 reports with diazepam as the "principal suspect (PS)" AEs were identified. Diazepam-induced AEs occurred targeting 27 system organ categories (SOCs). Based on four algorithms, a total of 391 major disproportionate Preferred Terms (PTs) were filtered out. Unexpectedly significant AEs such as congenital nystagmus, developmental delays, and rhabdomyolysis were noted, which were not mentioned in the drug insert. CONCLUSION: Our study identified potential signals of new AEs that could provide strong support for clinical monitoring and risk identification of diazepam.